DIFFERENT ALLELE-DISTRIBUTION OF MTHFR 677 C → T AND MTHFR −393 C → A IN PATIENTS CLASSIFIED ACCORDING TO SUBTYPES OF LESCH'S TYPOLOGY - BÖNSCH, DOMINIKUS; BAYERLEIN, KRISTINA; REULBACH, UDO; FISZER, ROLAND; HILLEMACHER, THOMAS; SPERLING, WOLFGANG; KORNHUBER, JOHANNES; BLEICH, STEFAN (Alcohol and alcoholism (Oxford), 2006)
Aims: The typology by Lesch distinguishes between four subtypes: type 1 (model of allergy), type 2 (model of anxiety or conflict), type 3 (alcohol as an antidepressant), and type 4 (alcohol as adaptation). Taking into account that alcohol dependence is associated with elevated homocysteine levels, this study was undertaken to investigate different MTHFR (methylenetetrahydrofolate reductase) genotypes related to homocysteine metabolism in patients with alcohol dependence who were classified according to Lesch's typology (LT). Subjects and methods: 134 non-abstinent chronic alcoholics (112 males, 22 females; mean age 44.2 (SD 8.9) years) were classified according to LT and divided into four groups: LT 1 (n = 26), LT 2 (n = 65), LT 3 (n = 58), and LT 4 (n = 18). Total plasma homocysteine levels and MTHFR genotypes −393, 677, and 1793 were determined. Results: We observed a significantly higher frequency of the thermolabile MTHFR 677 C→T variant (TT) in patients classified as subtype LT4 when compared with subtypes LT2 and LT3 (P = 0.005). Furthermore, for the MTHFR −393 C → A-polymorphism, significantly more AC/AA variants were found in subtype LT4 (P = 0.034). No differences in allele-distribution were detected for MTHFR 1793. Conclusion: To our knowledge, this is the first study evaluating MTHFR genotypes in patients who were classified according to LT. Significantly different distributions of MTHFR 677 and −393 variants within Lesch Type 4 as compared with Types 2 and 3 hint at genetic determination of Lesch subtypes.